Pengaruh Edukasi Gizi Berbasis Game Online Terhadap Pengetahuan Anak Sekolah Tentang Makanan Sehat - Lidia Fitri; Devin Mahendika; Juenita Elfunam Mado; Mahfuzhoh Fadillah Heryanda; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background: Elementary school children's nutritional knowledge remains low, potentially leading to unhealthy eating behaviors and long-term health risks. Traditional educational methods tend to be less engaging for children, necessitating an interactive approach that can enhance understanding and motivation to learn. Objective: This study aimed to evaluate the effect of online game-based nutrition education on school children's knowledge of healthy eating. Methods: The study used a quasi-experimental pre-test and post-test design with 60 students in grades 4-6 of elementary school in District X. The research instrument was a validated nutritional knowledge questionnaire consisting of 20 multiple-choice questions regarding healthy food types, balanced nutrition, and good eating habits. The intervention was conducted for 2 weeks, with each session lasting 20–30 minutes. Data were analyzed using a paired t-test with a significance level of p < 0.05. Results: The study showed a significant increase in students' nutritional knowledge scores after participating in online game-based education, with the average score increasing from 12.5 ± 3.2 to 17.8 ± 2.5 (p < 0.001). This indicates that the intervention was effective in improving children's understanding of healthy eating. Conclusion: Online game-based nutrition education has been shown to be effective in improving schoolchildren's knowledge of healthy eating. This method is recommended as a fun and interactive nutrition learning strategy, with long-term potential to shape healthy eating behaviors from an early age.